Budidaya Tanaman Hortikultura Memanfaatkan Lahan Pekarangan di Bunaken Manado - Ernest Hanny Sakul; Revolson Alexius Mege (DEDIKASI, 2019)
Bunaken Island which is shaped like the crescent, has an area of 696.8 ha and is a park conservation areanational sea in North Sulawesi. Bunaken Island has two villages, first, Bunaken Village, the administrative area ofup to Parigi Headland and Siladen Island. Then the second village is Alungbanua Village. Based on the surveyresults in the village of Bunaken- Parigi Headland, it was known that there are still many yards that are still not usedfor planting horticultural crops that can provide a food source for family. In addition, it was found that there werestill many pigs released wildly by the community and produced large amounts of pig manure. Parigi Headlandpeople have the potential to develop group and family businesses in agriculture, but still have limitations indeveloping farming technology, making and using organic fertilizers, and producing organic pesticides. PKMHorticultural Crop Cultivation Utilizing Yard Land in Bunaken Manado aims to train communities and families inthe village of Bunaken-Parigi Headland to be able to utilize their yard and increase the quantity and quality ofproduction of horticultural crops in the form of chili, tomatoes and vegetables. Furtheremore, it aims to guide andtrain the community so they can produce their own organic fertilizer as a result of fermentation of livestock manure.The results obtained were 1) an increase in public understanding of the importance of using yard land as a place offarming with high economic value such as chili, 2) results obtained by the early harvest chilies weight ranged from0.50 to 1.10 kg per plant in the raised beds, and the weight of chilies grown in polybags have a range of 0.40 to 0.95kg per plant, 3) organic fertilizer fermented manure waste using biological agents effective microorganism (EM4)was gained, and 4) the construction of the maintenance enclosure for pigs.